“Where You Are Accepted, You Blossom”: Toward Care Ethics in Jazz Historiography - Blais-Tremblay, Vanessa (Jazz & Culture, 2019)

Revitalising language through music: a case study of music and culturally grounded pedagogy in two Kanien’ke:ha (Mohawk) language immersion programmes - Vallejo, Jessie M. (Ethnomusicology Forum, 2019)
Since the 1990s scholars, teachers, and policy makers have debated over the importance of culturally grounded or culture-based education (CBE) approaches in primary and secondary programmes. For Indigenous communities, CBE methods are often regarded as decolonising tools that support linguistic and sociocultural revitalisation efforts. A majority of Indigenous educational projects have prioritised teaching language above other cultural components, such as music, which has largely been overlooked as a powerful tool due to the pervasive assumption that traditional musical practices rely on the language to survive. This article explores how cultural components have a symbiotic rather than a hierarchical relationship, focusing on the interdependence between language and music. Based on ethnographic fieldwork and observations with four Indigenous language immersion teachers, I argue that music is a linchpin pedagogical tool that promotes intergenerational interactions, builds social relationships, and facilitates the daily use of language in and outside the classroom.
Keywords: Haudenosaunee; Indigenous; Iroquois; culture-based education; decolonisation; language immersion

Jazz, gender, historiography: a case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
This dissertation maps the interaction between jazz, identity, modernity and nation during the so-called "golden age" of jazz in Montreal (1925-1955). Drawing on the fields of musicology, women's studies (black feminist theory and feminist research methods in particular), critical dance studies, and cultural studies, this project provides a critical re-writing of the history of Montreal jazz, one which acknowledges various roles that racialized and ethnicized women played in the shaping of modern identities, pleasures and sounds in Quebec. Montreal's particular status as a "showtown" makes it a rich laboratory to study the collaborative creative relationships between jazz music and dance on the black variety stage in the first half of the twentieth century. I also map the specific parameters that articulate the discursive relationship between jazz and vice, in particular as these relate to the gendered and racialized embodiment of morality in interwar Quebec. Finally, this dissertation produces the first extensive biographical accounts and critical listening of several prominent Montreal-based female jazz artists, including pianists Vera Guilaroff and Ilene Bourne, all-girl groups such as The Spencer Sisters and the Montreal Melody Girls Orchestra, black women performers such as Tina Baines Brereton, Bernice Jordan Whims, Marie-Claire Germain, Mary Brown, Natalie Ramirez, as well as piano teacher Daisy Peterson Sweeney and dance teachers Ethel Bruneau and Olga Spencer Foderingham.

A Rich Musical Legacy from Québec: Baroque Motets of the Ursuline and Hôtel-Dieu Monasteries of New France - MacIsaac, Elizabeth Kathleen Norah (Université de Washington, 2018)
Carefully preserved in the archives of the Ursuline and Hôtel-Dieu Monasteries of Quebec are several manuscripts containing Canada’s first sacred works for female voices. The manuscripts contain dozens of intricate motets composed in the French Baroque style, a repository of music which has not been sung for hundreds of years. These motets form a neglected part of Canada’s musical heritage which is waiting to be unearthed and explored. Ursuline and Augustinian nuns arrived to the French territories of the New World to educate and evangelize young women. Singing formed a core element of their teaching and worship. For over one hundred years (1639-1760), church music provided a backbone to Canada’s vibrant musical culture. When the French territories were lost to Britain and Spain, musical culture shifted radically and the sacred French music simply faded into obscurity. An overview of the sweeping events of the French Baroque era includes discussion of France’s social conditions, the political and religious climate, the flowering of the arts and the exploration of the New World. In France, the seventeenth and eighteenth centuries were a time of great strife which heralded the massive social changes to come in the nineteenth century. France’s struggles directly impacted the colony of New France, including that of its religious institutions and music. This study traces the musical activities in the Ursuline community of New France as the nuns lived their mission on the frontier, teaching Aboriginal and colonial girls. The evolution of female emancipation stemming from religious evangelism is considered. Examination of a trove of 160 motets located in the female monasteries of Québec City reveals the high caliber of music practiced by the nuns. No interpretive editions for performance purposes exist. Newly transcribed works have been generated from the manuscripts, with period performance guidance for appropriate ornamentation and ensemble requirements. An in-depth discussion of New France Baroque vocal and choral musical styles is provided, with reference to historical records of how it was taught, as described in contemporaneous music treatises and many original documents specific to these religious female communities.

Femmes et jazz dans le Québec de l’entre-deux-guerres : entre le récit historique, les archives et le passé - Blais-Tremblay, Vanessa (Les Cahiers de la Société québécoise de recherche en musique, 2017)
Cet article porte sur les rôles que les femmes ont joué dans le développement d’une scène jazz à Montréal. Les archives témoignent de l’importance des pianistes Vera Guilaroff et Ilene Bourne, de l’enseignante de piano Daisy Peterson Sweeney, des enseignantes de danse Olga Spencer Foderingham et Ethel Bruneau, ainsi que des danseuses de variétés dans le développement de la plus grande scène jazz du Canada au cours de la première moitié du xxe siècle. Cet article contextualise la présence des femmes dans ces espaces performantiels précis (le piano, l’enseignement, la danse) et explore les processus historiographiques liés à leur exclusion des récits historiques.

L'incertitude matérielle et existentielle de la carrière musicale au prisme des relations interpersonnelles - Rheault, Dominique (Université du Québec à Montréal, 2017)
La précarité du domaine musical professionnel au Québec se traduit pour les musicien-ne-s par l'expérience de l'incertitude matérielle et existentielle, conséquence d'un cadre d'emploi flexible (Bain et McLean, 2012). Ce mémoire vise à comprendre leur trajectoire professionnelle et se situe dans la perspective des études organisationnelles sur les carrières « sans frontières » (Arthur et Rousseau, 1996). La première forme d'incertitude rencontre la nécessité : 1) de développer un savoir/savoir-faire flexible à l'emploi; 2) de multiplier des métiers au sein du domaine musical; 3) et de cultiver un réseau professionnel. La seconde se définit par l'« équivocité » (Weick, 1995, 1996, 2005) et est liée : 1) à l'acquisition du savoir-être; 2) à la question du sens de la carrière; 3) et au soutien social. Nous inscrivons également cette recherche dans cette nécessité d'effectuer plus d'études empiriques sur le rôle des relations interpersonnelles dans la carrière musicale (Di Maggio, 2011; Cummins-Russell et Rantisi, 2012; Azam, 2014; Menger, 2014). Ainsi, comment vivent-elles-ils les incertitudes de la carrière musicale? En quoi leur réseau de relations interpersonnelles leur permet-il de les réduire? Cela nous a amenés à rencontrer six musicien-ne-s professionnel-le-s québécois-es pour les questionner sur leur parcours, leurs enjeux professionnels et cartographier leur réseau de collaboration selon la « méthode du générateur de noms » (Saint-Charles et al., 2008) et plus largement la démarche de analyse de réseaux sociaux (Wasserman et Faust, 1995). Nos résultats indiquent que la réduction de l'incertitude matérielle passerait par un processus de professionnalisation aux frontières des organisations du domaine musical et l'entretien de relations interpersonnelles de confiance. Pour elles/eux, la carrière musicale se distingue des carrières « typiques » puisqu'il s'agit surtout d'une « histoire de passion » où le succès professionnel est déterminé par la capacité à se lier aux autres et à vivre cette « expérience de sociabilité » du domaine musical. Ce mémoire vise à explorer un phénomène peu documenté et à identifier certaines pistes de recherches futures sur ce sujet.

Bilan et perspectives sur la situation des compositrices au Québec : vers un décloisonnement des identités - Tremblay, Vicky (Les Cahiers de la Société québécoise de recherche en musique, 2017)
In the field of composition in Quebec, women composers are still less numerous than men composers. While the profession of composer has difficulty being recognized in Quebec society, women composers are twice as marginalized. Many of give evidence to the challenges they face when it comes to integrating into the musical community, and several musicologists have tried to better understand—and eventually solve—the problems specific to women in the field of composition.

Animating the Object: Marcelle Deschênes and acousmatic education in Quebec - Valiquet, Patrick (Organised Sound, 2017)
This article examines the early reception of Pierre Schaeffer’s theoretical work in Quebec through the teaching of Marcelle Deschênes, principal author of the first electroacoustic theory and ear training curricula at both Université Laval and Université de Montréal. An account of Deschênes’s educational career is provided, along with remarks on the contents of her early courses in Morpho-typology and her listening workshops for children, using newly excavated primary material from her private archives. While existing scholarship presumes that Schaefferian thinking arrived in Quebec with the ‘orthodox’ acousmatic approach of Francis Dhomont, this article asserts that a pluralist and multidisciplinary interpretation of Schaeffer’s work can be discerned which pre-dated Dhomont’s teaching and has had an equally lasting impact overall. A methodological argument is also made for including education and other forms of ‘reproductive labour’ in the history of electroacoustic music.

Providing the Taste of Learning: Nadia Boulanger’s Lasting Imprint on Canadian Music - Boivin, Jean (Intersections: Canadian Journal of Music / Intersections : revue canadienne de musique, 2013)
This article traces the rich Canadian legacy of the twentieth-century French musical legend Nadia Boulanger (1887–1979). Through teaching her more than seventy Canadian students, both French- and English-speaking, the renowned French pedagogue played a crucial role in the development of concert art music in this country from the 1920s, notably in Montreal and Toronto. Her numerous Canadian students went on to distinguish themselves as composers, teachers, performers, musicologists, theorists, administrators, and radio producers. Drawing on extensive archival and primary research, this study demonstrates the decisive impact Boulanger had on the development of musical styles and compositional practices in Canada in the last century.

Maryvonne Kendergi (1915-2011) : hommage et mémoire - Bail, Louise (Circuit, 2012)

Life notations of Daisy Sweeney: reflections of othermothering, musicianship and Montreal - Campbell, Arlene (Université York, 2012)
The life story of Mrs. Daisy Sweeney, an African Canadian native of Montreal, Quebec, helps fill a void in the historical documentation of Montreal Blacks (especially female elders). Of particular significance is her prominence as a music educator and othermother during her life. The current literature on African Canadian othermothering experiences is not synonymous with both White or African American females and inclusion of their voices in academic, as well as mainstream spaces, is virtually non-existent. This dissertation asks: What did it mean to be a first generation 'Negro' working class bilingual female in a largely hostile White francophone Quebec metropolis in the early 20th Century? How can her narratives help shape and inform life history and African Canadian othermothering research? My sojourn with Mrs. Daisy Sweeney referenced African centered epistemology in my conceptual understanding of herself and community mothering. Capturing her conversations meant engaging with multiple methodologies articulated through African oral traditions, life history, archival canons and interdisciplinary inquiries. It is striking to note that there were not only certain tensions associated with memory loss and physical limitations (prompted by the aging process) that destabilized and enriched our 'interactive' communication, but also revealed a rupture and reversal of the participant/researcher dynamic. In spite of blatant racial discrimination that plagued Montreal's Black communities during that time, Daisy Sweeney fulfilled a life-long dream and taught hundreds of children the canon of classical piano for over 50 years. She lived her voice through her music, finding ways to validate her own identity and empowering others in the process. She used the musical stage as her platform to draw invaluable connections between race, gender, language and social class. Daisy Sweeney's generation of othermothers is dying out and, as the carriers of culture, the urgency to tell their stories must be emphasized. The account respects, reclaims and reflects those voices. It is time to write in African Canadian female elders and diversify the exclusionary genre of life history and archival research.

La réalité socioprofessionnelle des musiciennes au Québec : un engagement vers l’écriture du féminin - Stévance, Sophie (Loin des yeux près du corps. Entre théorie et création, 2012)

Ethel Bruneau: Montreal’s Rhythm Tap Legend - Lys, Stevens (Dance Collection Danse, 2011)